Abnormal muscle afferent function in a model of Taxol chemotherapy-induced painful neuropathy - Chen, Xiaojie (American Physiological Society, 2011)
Despite muscle pain being a well-described symptom in patients with diverse forms of peripheral neuropathy, the role of neuropathic mechanisms in muscle pain have received remarkably little attention. We have recently demonstrated in a well-established model of chemotherapy-induced painful neuropathy (CIPN) that the anti-tumor drug paclitaxel (Taxol) produces mechanical hyperalgesia in skeletal muscle, of similar time course to and with shared mechanism with cutaneous symptoms. In the present study, we evaluated muscle afferent neuron function in this rat model of CIPN. The mechanical threshold of muscle afferents in rats exposed to paclitaxel was not significantly different from the mechanical threshold of muscle afferents in control animals (P = 0.07). However, paclitaxel did produce a marked increase in the number of action potentials elicited by prolonged suprathreshold fixed intensity mechanical stimulation and a marked increase in the conduction velocity. In addition, the interspike interval (ISI) analysis (to evaluate the temporal characteristics of the response of afferents to sustained mechanical stimulation) showed a significant difference in rats treated with paclitaxel; there was a significantly greater ISI percentage of paclitaxel-treated muscle afferents with 0.01- and 0.02-s ISI. In contrast, an analysis of variability of neuronal firing over time (CV2 analysis) showed no effect of paclitaxel administration. These effects of paclitaxel on muscle afferent function contrast with the previously reported effects of paclitaxel on the function of cutaneous nociceptors.